2022
DOI: 10.1002/aic.17931
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum sequestration empowers phosphorylation profiling on the yeast surface

Abstract: Cells sense cues in their surrounding environment, turning extracellular stimuli into intracellular responses. Transient posttranslational modifications, such as phosphorylation, often guide these responses through tightly regulated signaling networks.There is great interest in understanding phosphorylation events that yield responses in cell signaling, but to date, methods to characterize the phosphoproteome rely on low-throughput methods. To overcome this limitation, this study optimizes a yeast surface disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Importantly, it was shown that ponatinib remained effective against most single mutants of ABL1 kinase, with drug resistance starting only with rare compound mutations. Ezagui et al (2022) recently harnessed ER sequestration to measure tyrosine phosphorylation cascades using full‐length protein substrates. Using a modified version of the YESS plasmid containing a ribosomal skipping sequence (T2A), the protein‐tyrosine kinase (LCK) is expressed and activates ZAP‐70, an intermediate enzyme, through phosphorylation of its catalytic loop.…”
Section: Yeast Er Sequestration Accurately Quantifies Ptm–enzyme Cata...mentioning
confidence: 99%
“…Importantly, it was shown that ponatinib remained effective against most single mutants of ABL1 kinase, with drug resistance starting only with rare compound mutations. Ezagui et al (2022) recently harnessed ER sequestration to measure tyrosine phosphorylation cascades using full‐length protein substrates. Using a modified version of the YESS plasmid containing a ribosomal skipping sequence (T2A), the protein‐tyrosine kinase (LCK) is expressed and activates ZAP‐70, an intermediate enzyme, through phosphorylation of its catalytic loop.…”
Section: Yeast Er Sequestration Accurately Quantifies Ptm–enzyme Cata...mentioning
confidence: 99%
“…Importantly, Taft showed that ponatinib remained effective against most single mutants of ABL1 kinase, with drug resistance starting only with rare compound mutations. Stern and colleagues recently harnessed ER sequestration to measure tyrosine phosphorylation cascades using full-length protein substrates (Ezagui et al, 2022). Using a modified version of the YESS plasmid containing a ribosomal skipping sequence (T2A), the protein-tyrosine kinase (LCK) is expressed and activates ZAP-70, an intermediate enzyme, through phosphorylation of its catalytic loop.…”
Section: Ptm-enzyme Assays Beyond Proteasesmentioning
confidence: 99%
“…Furthermore, YESS allows the user to measure enzyme activities directly on the cell surface, rather than transcriptional signal amplification (Sanchez and Ting 2020). YESS is an all-in-one platform that allows one to engineer and profile the substrate specificity of PTM-enzymes while also enabling highthroughput drug screening deep mutational scanning assays (Yi, Gebhard et al 2013, Yi, Taft et al 2015, Ezagui, Russell et al 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been used in conjunction with machine learning to predict the substrate preference and binding energy of hepatitis C virus (HCV) protease (Pethe, Rubenstein et al 2019). More recently, YESS was used to assay histone acetyltransferase activities (Waldman, Rao et al 2021) and crosstalk and to recapitulate mammalian phosphorylation cascades (Ezagui, Russell et al 2022).…”
Section: Introductionmentioning
confidence: 99%